2018
DOI: 10.1038/s41598-017-18797-7
|View full text |Cite
|
Sign up to set email alerts
|

New live screening of plant-nematode interactions in the rhizosphere

Abstract: Free living nematodes (FLN) are microscopic worms found in all soils. While many FLN species are beneficial to crops, some species cause significant damage by feeding on roots and vectoring viruses. With the planned legislative removal of traditionally used chemical treatments, identification of new ways to manage FLN populations has become a high priority. For this, more powerful screening systems are required to rapidly assess threats to crops and identify treatments efficiently. Here, we have developed new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 113 publications
1
28
0
Order By: Relevance
“…These small losses of resolution at 100 µm depth in both Nafion and cryolite TS microcosms relative to at the coverslip were statistically significant ( Figure 3F ; n = 8 beads per category, one-way ANOVA of all three categories F-statistic 19.904, p-value=1.418×10 −16 ; Tukey-Kramer HSD p-value=8.6×10 −6 for coverslip versus Nafion and p-value 0.01014 for coverslip versus cryolite; bootstrap p-value testing difference in means 0.0006001 for coverslip versus Nafion and 0.003200 for coverslip versus cryolite). Thus, although previous work focused on closer RI matching of TS particles and liquid in order to improve image quality through the particle matrix ( Downie et al, 2012 ; Leis et al, 2005 ; O'Callaghan et al, 2018 ), we found that exact RI matching was not necessary to obtain well-resolved images of 1 µm-diameter fluorescent objects even through 100 µm of TS, suggesting that even micron-sized bacteria could be imaged in both Nafion and cryolite TS microcosms to considerable depth.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…These small losses of resolution at 100 µm depth in both Nafion and cryolite TS microcosms relative to at the coverslip were statistically significant ( Figure 3F ; n = 8 beads per category, one-way ANOVA of all three categories F-statistic 19.904, p-value=1.418×10 −16 ; Tukey-Kramer HSD p-value=8.6×10 −6 for coverslip versus Nafion and p-value 0.01014 for coverslip versus cryolite; bootstrap p-value testing difference in means 0.0006001 for coverslip versus Nafion and 0.003200 for coverslip versus cryolite). Thus, although previous work focused on closer RI matching of TS particles and liquid in order to improve image quality through the particle matrix ( Downie et al, 2012 ; Leis et al, 2005 ; O'Callaghan et al, 2018 ), we found that exact RI matching was not necessary to obtain well-resolved images of 1 µm-diameter fluorescent objects even through 100 µm of TS, suggesting that even micron-sized bacteria could be imaged in both Nafion and cryolite TS microcosms to considerable depth.…”
Section: Resultsmentioning
confidence: 73%
“… Downie et al, 2012 ; Downie et al, 2014 then demonstrated that plant roots with native-like architectures could be grown and visualized in Nafion-based TS ( Downie et al, 2012 ). Surprisingly, given the novel visualization abilities it provides, the Nafion TS system has only been sparsely utilized for studying biological systems ( Downie et al, 2014 ; Downie et al, 2012 ; O'Callaghan et al, 2018 ). This may be due to (a) the high cost of Nafion and (b) the RI of Nafion (RI = 1.35; Leis et al, 2005 ) not matching water closely enough (RI = 1.333) to allow deep (millimeter to centimeter) imaging.…”
Section: Introductionmentioning
confidence: 99%
“…There are of course advantages of using synthetic materials to mimic soil structures for microbiological studies. Ground pellets of Nafion (a sulfonated tetrafluoroethylene polymer) have been used as a substrate for cultivating plants and imaging root-microbe and root-nematode interactions [40] , [17] , [16] . Because these pellets have a refractive index similar to water, Nafion “soil” columns become optically transparent when saturated with water, allowing brightfield and fluorescence imaging of the plant roots and associated organisms in the structured matrix.…”
Section: Recent Methods For Investigating Microbial (Micro)environmenmentioning
confidence: 99%
“…In this respect, the application of transparent soil represents an innovative approach to study and live image microbes on plant roots in an environment which mimics different soil textures ( Downie et al, 2012 ). It allows to detect processes driving the distribution of microbes in bulk substrate along the root ( Downie et al, 2014 ) and study the effects of major root pests such as nematodes on microbe/community behavior ( O’Callaghan et al, 2018 ).…”
Section: Experimental Set Ups To Study Microbiomesmentioning
confidence: 99%